A detailed simulation-based study on the effect of mirror integration on PV Module(s) with analysis of different wind flow scheme. (1st July 2021) - Agrawal, Monika; Kumar, Avinash; Chowdhury, Amartya
Highlights: Improved passive cooling of the PV module through understanding of wind speed and flow direction. Effect of air turbulence on module temperature. More power generation of PV module with reflector system in the reduced operating lifespan. Abstract: The effective use of the available land in a PV power plant can be obtained by the integration of a commonly available flat stainless-steel reflector. The integration of the reflector increases module temperature and simultaneously the degradation rate. In this regard, the present work proposes a 3-D opto-thermal simulation model to analysis the performance of the commercial C-Si PV module with stainless steel (SS) reflector. The study also highlights that the natural flow of wind effectively reduces the elevated temperature and the direction of wind flow plays a very prominent role in heat evacuation. Incidentally, the largest state of India, Rajasthan has plenty of promising light breeze throughout the year and that is to come from the mostly north or west direction. A simpler version of the proposed model was experimentally validated in the month of July in Jaipur, India. The simulation result shows that the reflector induces 30 °C to 40 °C increment in temperature in the PV module for laminar airflow. Considering the turbulent airflow model, the temperature rise is 10–20 °C. The thermal scenario largely depends on wind flow and the season considered. The lifetime of the PV module is reduced from 25 years to 21 years with the integration of reflector at favorable wind flow condition. However, it generates a significantly more electric power which overcomes the lifetime loss.